Paclitaxel‐eluting balloon versus everolimus‐eluting stent for treatment of drug‐eluting stent restenosis. Issue 6 (3rd July 2013) - Almalla, Mohammad; Schröder, Jörg; Pross, Verena; Marx, Nikolaus; Hoffmann, Rainer
<x xml:space="preserve">Abstract</x> Objective Drug‐eluting stent (DES) implantation is a very effective treatment of bare‐metal stent–in‐stent restenosis (BMS–ISR). Therapeutic options for drug‐eluting stent–in‐stent restenosis (DES–ISR) are less well defined, as there are only few data on safety and effectiveness of interventional modalities. This study compared the 1‐year clinical outcome after the use of drug‐eluting balloon (DEB) to second‐generation everolimus‐eluting stent (EES) for treatment of DES–ISR. Methods This observational study included 86 patients with 86 DES–ISR. Forty patients were treated by repeat percutaneous coronary intervention (PCI) using an EES. Forty‐six patients were treated by repeat PCI using a DEB. Follow‐up periods were 22 ± 11 and 25 ± 19 months, respectively. The primary endpoint of the study was survival free of major adverse cardiac events (MACEs) at 1 year. Secondary endpoints were needed for target lesion revascularization (TLR), definite stent thrombosis (ST) at 1 year, and MACE rate during total follow‐up period. Results Baseline clinical and angiographic parameters were comparable between the two groups. EES were associated with a higher MACE rate at 1 year compared to DEB (27.5 vs. 8.6%, respectively; P = 0.046). TLR rates for EES and DEB were 22.5% versus 4.3%, respectively, P = 0.029, while rates of definite ST at 1 year follow‐up were comparable (2.5% vs. 0%, respectively; P = 0.945). There were no differences in myocardial infarction rates between the two groups (5% vs. 2%, respectively; P = 0.595) and in mortality. Considering the complete follow‐up periods, DEB were associated with significantly less MACE compared to EES (log‐rank test, P = 0.045). Furthermore, comparison of TLR rates showed a strong trend in favor of DEB compared to EES (P = 0.074). Conclusions Treatment of DES‐ISR using a DEB is associated with favorable rates of MACE and TLR at 1‐year follow‐up compared to the implantation of an EES. © 2013 Wiley Periodicals, Inc.